Converting sludge into a valuable product – biochar - Mak, Nicole Xiu Ting (Nanyang Technological University, 2022)
Production of sludge during wastewater treatment processes poses a major challenge due to its large production volume and presence of hazardous substances, like heavy metals (HMs) and pathogens. It is conventionally dewatered to be incinerated and the ashes are disposed of in landfills. However, rather than being a waste product, sludge is a valuable resource that has uses in energy and resource recovery. Sludge is generally high in organic matters and rich in nutrients and trace minerals. One sustainable method of utilising sludge is through pyrolysis to convert it into biochar which is a potential soil amendment. Biochar can undergo steam activation and be converted to activated carbon (AC) with higher surface area and pore volume which is a potential low-cost adsorbent.